Molecular detection of Borrelia spp. (Spirochaetales: Borreliaceae) in ticks (Acari: Ixodidae) collected from tortoises in Java, Indonesia - HANA FAIZAH SOPHIA; SUPRIYONO SUPRIYONO; SUSI SOVIANA; DIMAS NOVIANTO; UPIK KESUMAWATI HADI (Society for Indonesian Biodiversity, 2023)
Abstract. Sophia HF, Supriyono, Soviana S, Novianto D, Hadi UK. 2023. Molecular detection of Borrelia spp. (Spirochaetales: Borreliaceae) in ticks (Acari: Ixodidae) collected from tortoises in Java, Indonesia. Biodiveritas 24: 6852-6857. Reptiles are known hosts of various tick species, many of which are zoonotic and pose veterinary and public health risks. Amblyomma ticks frequently parasitize reptiles and are potential vectors of zoonoses. This study aimed to investigate the prevalence of tick infestations and to identify Borrelia species infections in ticks found on tortoises. One hundred six tortoise hosts in three provinces in Indonesia. DNA extraction and Borrelia species were detected using conventional PCR techniques. The results revealed the presence of nineteen hard-bodied ticks on Chelonoidis carbonarius Spix, 1824, Chelonoidis denticulatus Linnaeus, 1766, and Geochelone sulcata Miller, 1779. All the ticks collected were identified as Amblyomma sparsum Neumann 1899, and the prevalence of A. sparsum infestations on tortoises in this study was 7.55%. Borrelia spp. was detected in some of the A. sparsum ticks infesting tortoises. Subsequent sequencing unveiled two distinct reptile-associated (REP) borrelia strains. This study sheds light on the tick infestation patterns and the potential transmission of Borrelia species among tortoises kept as exotic pets in urban areas by A. sparsum ticks. The findings provide valuable insights into the bioecology of ticks and the associated health risks they pose to reptiles, thereby contributing to our understanding of zoonotic disease dynamics in the region.